Mediating acid-catalyzed conversion of levoglucosan into platform chemicals with various solvents - Hu, Xun; Wu, L.; Wang, Yi; Mourant, Daniel; Lievens, Caroline; Gunawan, Richard; Li, Chun-Zhu (The Royal Society of Chemistry, 2012)
Acid-catalyzed conversions of levoglucosan have been investigated in mono-alcohols, poly-alcohols, water, chloroform, toluene, acetone, N,N-dimethyl formamide, dimethyl sulfoxide and some mixed solvents, aiming to mediate conversion of sugars into platform chemicals with solvents. The mono-alcohols can stabilize soluble polymers and thus suppress formation of insoluble polymers. Water does not have such an effect, leading to lower yields of levulinic acid. Chloroform cannot effectively dissolve levoglucosan, leading to “dissolving” of levoglucosan in the catalyst and the consequent rapid polymerization. Acetone reacted with sugars, forming substantial amounts of polymer. N,N-Dimethyl formamide poisoned the acid resin catalyst, leading to negligible conversion of levoglucosan. Dimethyl sulfoxide (DMSO) mainly catalyzed the conversion of levoglucosan into 5-(hydroxymethyl)furfural (HMF), 2,5-furandicarboxaldehyde, and the sulfur ether of HMF. DMSO has a low ability to transfer protons, which helps to avoid further contact of HMF with catalytic sites and stabilizes HMF.